Drinking Water Supply Control and Water Theft Identification System - M.Harsha Priya, Shaik. Kaja Rahamtulla (International Journal of Scientific Research and Management (IJSRM), 2013)
The fast growing of the broad urban residential areas imposes the expansion as well as the sophistication of the present water supply facilities. Along with this one more problems is recognized in the water supply channels, some people use ½ HP to 1 HP pump to suck the water directly from the channel of their home street. This automation system based upon utilization of an electronic sensor unit ESU and PC systems including all the network components like Zigbee helps us the best way to improve the water distribution technological process. The theft of water can be best monitored by the flow variations calculated by the flow sensors mounted on the channels. The system includes Remote Terminal Units – RTU, specific transducers distributed on a wide geographical area and control and power panels for the pump stations. The reliable instrumentation connected to Electronic Sensor Unit ESU or RTU assure real time monitoring of the main technological parameters of large water distribution networks. The data acquired of SCADA system (Supervisory Control and Data Acquisition) signify the support for optimization of the process and data- driven decision Support System. The system uses a monitoring system implemented on PC to ensure the process supervision and remote control functions based on UART technologies and wireless communication components for WAN data transfer. The complete SCADA system for water distribution enable the user to get a high operation safety of the network, a cost effective use of equipment, energy efficiency and optimize the daily operation and maintenance procedures.